Revisión sistemática: caracterización de microorganismos presentes en los núcleos colados usados en procedimientos intrarradiculares (2020)
Introduction: The lack of asepsis in the materials used in intraradicular procedures becomes a gateway to microorganisms that can trigger complex infections that could place the patient's health at imminent risk. Objective: To carry out a systematic review to characterize the presence of microorganisms present in the cast nuclei used in intradicular procedures. Materials and Methods: It is a secondary research, which will be carried out from a systematic review which aims through an exhaustive analysis of scientific articles, make a detailed characterization of the variables of study to respond to the objectives set out in the research. Results: 47% of the microorganisms found in the review correspond to the group of positive Gram Anaerobia, followed by 32% that belong to the Negative Gram Anaerobia, 11% that belong to the negative Gram Bacillus, 5% to the positive Gram Bacillus and the other 5% to the Positive Gram Aerobia. Conclusions: If the strained nuclei are not worked under aseptic protocols, they can become carriers of microorganisms that lead to treatment failures and the appearance of new pathologies as a consequence of the presence of microorganisms.